ANALISISTINGKATKEPUASANKONSUMEN PADA RESTORAN CEPATSAJI MENGGUNAKAN FUZZY MAMDANI - Eko Wijaya; Desi Arisandi; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
The development of technology is the root of the civilization of society in carrying out their daily activities. In its application, technology can make it easy to access information that helps people to find out certain information, one of which is the level of consumer satisfaction with fast food restaurants.Fast food restaurants have become an important factor in people's daily activities. To fulfill its role in people's lives, fast food restaurants serve food and services for their consumers. Fast food restaurants with decent service, as well as good food prices and quality will certainly result in a high level of satisfaction from consumers with these fast food restaurants.The Fuzzy Mamdani method is one part of the Fuzzy Inference System which is useful for drawing conclusions or the best decisions in uncertain problems. In its application, the criteria for fast food restaurants become variables to determine the level of consumer satisfaction with these fast food restaurants. The Fuzzy Mamdani method forms a fuzzy set of input variables, then implements the implication function, then composes the rules, then defuzzy to get the level of consumer satisfaction with fast food restaurants. In determining the level of customer satisfaction, Fuzzy Mamdani obtained an accuracy rate of 100%.